2023
DOI: 10.3390/foods12040709
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Nutrient Retention during Thermal-Assisted Hydration of Lupins

Abstract: Lupin, an arid pulse, is gaining popularity as a super food due to its superior nutritional properties. However, it has not been considered for large scale thermal processing, e.g., canning. The present work evaluated the best time/temperature combination to hydrate lupins for canning with minimum losses of bioactive nutrients, pre-biotic fibre, and total solids during hydration. The two lupin species showed a sigmoidal hydration behaviour, which was adequately modelled by the Weibull distribution. The effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Perera and co-workers reported that hydration significantly increases the RFOs content in hydration water of two lupin varieties in the range of 20-80 times [11]. The study highlighted the dominant role of temperature in causing RFO to leach out during hydration.…”
Section: Bean Hydration Processmentioning
confidence: 84%
See 2 more Smart Citations
“…Perera and co-workers reported that hydration significantly increases the RFOs content in hydration water of two lupin varieties in the range of 20-80 times [11]. The study highlighted the dominant role of temperature in causing RFO to leach out during hydration.…”
Section: Bean Hydration Processmentioning
confidence: 84%
“…During imbibition, the water travels into the internal structures of the grain, leading to swelling and softening of the cell walls and tissues [9,13]. Grains are porous media consisting of a complex network of microscopic cracks and crevices, which can take the form of intercellular spaces or dents on the starch, proteins, or cell wall polysaccharide networks [11,14]. These pores are the major water uptake pathways during the imbibition process.…”
Section: Bean Hydration Processmentioning
confidence: 99%
See 1 more Smart Citation